Contribution of Indonesian Women Migrant Workers (TKIP) to Child Welfare - Maria Ulfah Anshor (Jurnal Perempuan, 2017)
This article is part of dissertation research on childcare of Indonesian Women Migrant Workers (TKIP) in pesantren, using a qualitative approach and analysis unit in child and their environment. This study uses the ecological system theory of Bronfenbrenner and theconcept of Global Care Chain with the perspective of child protection. The results showed that the children of TKIP who abandoned by their mothers abroad became losing care, disrupted their social welfare psychically and socially; there is interdependence between the child’s of TKIP and his/her family with TKIP abroad; pesantren is an option for TKIP family because there is no professional childcare for the children of TKIP when their mother abandons her/him. Institutionally pesantren has potential to break the Global Care Chain injustice on the care of TKIP children with the support of religious values and traditions of pesantren. However, policy support is needed to ensure the care and social welfare of TKIP’s children that based on community and which integrated comprehensively inblueprint of Indonesian migrant worker policy.